INCLUSIVE EDUCATION IN THE UNIVERSITY EXTENSION COURSE: STRATEGIES, RESOURCES AND TEACHING MATERIALS IN MATHEMATICS TEACHING FOR STUDENTS OF BASIC EDUCATION WITH VISUAL DEFICIENCY - Uliana, Marcia Rosa; Leite, Eliana Alves Pereira (Jornal Research and Practice on Inclusive Education, 2019)
The present report refers to the 30-hour university extension course that was held at the Federal University of Rondônia Foundation (UNIR), Campus of Ji-Paraná between October 2016 and February 2017. The actions were organized as follows form: Periodic meetings; Planning and preparation of teaching materials for the teaching of Mathematics for students with visual deficiency; Testing of materials developed with students with visual deficiency; Guidance in the elaboration of a scientific article derived from the experience. The aim of the course was to enable teachers and future Mathematics teachers to discuss and reflect on the inclusion of students with visual deficiency (low vision and blind) in Basic Education and to develop/prepare didactic materials to meet the educational demands of this group of students. Thirteen lecturers from the UNIR Mathematics Degree Course, Ji-Paraná Campus, and two Basic Mathematics teachers who work in state schools of the city participated. Among the contributions of the course, we highlight the reflections and the instrumentalization of how to teach mathematics to students with visual deficiency, providing the construction of new knowledge about the pedagogical practice in a way that attends to human diversity in Basic Education.